BREAK FROM THE SCREEN: MENJAGA KESEHATAN MENTAL DI ERA DIGITAL - Samuel Adiprasetya Isaputra; Teguh Lesmana; Helsa Helsa; Allegra Tayori (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2025)
The Child Welfare Institution (LKSA) X is currently facing a serious issue related to social media addiction among its residents. Most of the residents, who are elementary to high school-aged children and adolescents, have begun accessing social media continuously. This behavior has affected their study time, self-confidence, and social relationships. In response, a service program in the form of a training was conducted to raise awareness of the signs of social media addiction and strategies to prevent and reduce its impact. The training methods included simulations, reflections, and group discussions, encouraging both residents and staff to find contextually appropriate ways to manage social media use. Participants were also given space to share their daily challenges and co-create solutions. The training’s effectiveness was evaluated using a pre-test and post-test Social Media Addiction Scale adapted by Agung and Sahara (2023). The analysis showed a decrease in average social media addiction scores, although not statistically significant. These results indicate a positive impact of the training, suggesting the need for a longer intervention period and further evaluation to ensure lasting outcomes.